Genetic variability, heritability and genetic advance in bitter gourd (Momordica charantia L.) (Indian Journal of Arid Horticulture, 2025)
Greater diversity in the initial breeding stock increases the likelihood of developing desirable crop varieties. The key aim of germplasm conservation is to gather and safeguard genetic variation in native crop species for both current and future breeding efforts. The analysis of variance revealed significant differences among the hybrids across all traits studied, with average performance data presented for 10 genotypes that exhibited low, moderate, and high levels of phenotypic (PCV) and genotypic coefficient of variation (GCV). The greatest GCV was observed for sex ratio (20.93%) and the number of primary branches per plant (21.30%). Traits such as number of seeds per fruit (17.93%) and fruit yield per plant (17.53%) showed moderate GCV, whereas lower GCV values were recorded for days to first staminate flower anthesis (8.78%) and fruit circumference (7.74%). In general, PCV values exceeded GCV values. Heritability was high for days to first staminate flower anthesis (85%), moderate for vine length (53%), and low for number of seeds per fruit (25%). Traits like number of primary branches per plant exhibited high heritability along with high genetic advance, suggesting the predominance of additive gene action.  Genetic advance expressed as a percentage of the mean was high for fruit yield per plant (41.79%) and number of primary branches per plant (40.55%). Moderate genetic advance was seen in traits like internodal length (18.67%), highlighting their considerable potential for improvement through direct selection.